Impact of Customer Retention Practices on Firm Performance in the Retailing Sector: A comparison between a foreign and home grown retailer in Malaysia (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
As customers are the backbone of any business, firms without customers would not be able to sustain their performance. This is because such firms are believed to have no revenues, no profits and therefore no market value. Accordingly, managing customers is deemed to be very crucial business agenda in which the key focus has been switched in recent years from attracting new customers to preserving existing ones. Both practitioners and scholars have discovered that it is much easier and cheaper to retain the exiting customers than investing on the potential customers. A decent customer retention level is believed to be a significant contributor towards improvement in the overall firm performance. A glimpse on the existing researches on customer retention highlights that financial sector has been thoroughly investigated which leave a room for a detailed investigation on customer retention within retailing sector. Accordingly, this study intends to explore the customer retention practices adopted by service-oriented firms in general and retailers in particular. As a comparison study on a foreign and home grown retailer, this study examines factors that retain customers and the subsequent impact of retention practices on firms performance. This study had carried out mall-intercept surveys among 400 shoppers at two major retailers within Klang Valley, Malaysia. Findings show that influencing factors of retention practices and type of retailer (namely foreign and home grown) significantly influences the retailers customer retention practices. It was also discovered that the inclusion of retailers type had enhanced the relationship between influencing factors and retailers retention practices. In addition, it was also found that customer retention practices significantly affect retailers performance at a moderate level. This study has uncovered that customers are in deed price sensitive despite being loyal and retained by firms. Hence, it is advisable for retailers to pursue a genuine pricing strategy to appeal to price conscious customers. The pricing strategy ideally should be transparent (i.e. no-bogus sales), clarity (i.e. provide accurate details of merchandises), simplicity (i.e. avoid psychological pricing) and trustable (i.e. provide accurate balances).